Temporal Changes in Fecal Unabsorbed Carbohydrates Relative to Perturbations in Gut Microbiome of Neonatal Calves: Emerging of Diarrhea Induced by Extended-Spectrum β-lactamase-Producing Enteroaggregative Escherichia coli - He, Zhiyuan; Ma, Yulin; Chen, Xu; Yang, Sirui; Zhang, Shuyuan; Liu, Shuai; Xiao, Jianxin; Wang, Yajing; Wang, Wei; Yang, Hongjian; Li, Shengli; Cao, Zhijun (Frontiers in Microbiology, 2022)
Early gut microbiota development and colonization are crucial for the longterm health and performance of ruminants. While, cognition of those microbiota is still vague, especially among neonatal dairy calves. Here, extended-spectrum β-lactamase producing enteroaggregative E. coli (ESBL-EAEC)-induced temporal changes in diversity, stability, and compostitions of gut microbiota were investigated among neonatal female calves, with the view of discerning potential biomarkers of this arising diarrhea cases in local pastures. Nearly 116 newborn calves were enrolled in this time-period study during their first 2 weeks of life and a total of 40 selected fecal samples from corresponding calves were used in this study. The results revealed that differentiated gut microbiome and metabolome discerned from neonatal calves were accompanied with bacterial infection stage over time. Commensal Butyricicoccus, Faecalibacterium, Ruminococcus, Collinsella, and Coriobacterium, as key microbial markers, mainly distinguished “healthy” and “diarrheic” gut microbiome. Random forest machine learning algorithm indicated that enriched fecal carbohydrates, including rhamnose and N-Acetyl-D-glucosamine, and abundant short-chain fatty acid (SCFA) existed in healthy ones. In addition, Spearman correlation results suggested Butyricicoccus, Faecalibacterium, Collinsella, and Coriobacterium as key commensal bacteria of healthy calves positively relative to highly productions of unabsorbed carbohydrates, SCFAs, and other prebiotics, and negatively correlated to increased lactic acid, hippuric acid, and α-linolenic acid. Our data suggested that ESBL-EAEC induced diarrhea in female calves could be forecasted by gut microbiome alterations and markedly changed fecal unaborbed carbohydrates during early lives, which might be conducive to early interventions to ameliorate clinic symptoms of diarrhea induced by the rising prevalence of ESBL-EAEC.